2019
DOI: 10.1002/adem.201900702
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Mechanical Behavior of Cu/Nb Multilayer Composites Processed by Accumulative Roll Bonding

Abstract: Cu/Nb multilayer composites with minimum individual layer thicknesses of ≈2.8 μm are achieved by accumulative roll bonding (ARB). The microstructural evolution and mechanical properties of these composites are investigated with different layer thicknesses after ARB processing. The results show that there is no visible interfacial reaction between the Cu and Nb layers, and the kernel average misorientation (KAM) distributions in electron backscatter diffraction (EBSD) maps remain in steady state during the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 67 publications
(172 reference statements)
0
6
0
Order By: Relevance
“…This change in deformation path affects significantly the grain refinement and then the mechanical properties such as the tensile strength [22][23][24][25][26]. ARB processing is a useful method for manufacturing metal matrix composite materials and for multilayer composite materials such as Al/B4C [23], Al/Mg [27], and Cu/Nb [28] or with more than two different materials like Al/Ti/Nb [29] and Al/Cu/Mg [30].…”
Section: Introductionmentioning
confidence: 99%
“…This change in deformation path affects significantly the grain refinement and then the mechanical properties such as the tensile strength [22][23][24][25][26]. ARB processing is a useful method for manufacturing metal matrix composite materials and for multilayer composite materials such as Al/B4C [23], Al/Mg [27], and Cu/Nb [28] or with more than two different materials like Al/Ti/Nb [29] and Al/Cu/Mg [30].…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Because the existence of a large number of laminated interfaces can be conducive to obstacles, dislocation mobility, and crack propagation. 32,33 More importantly, of the two basal planes typically present in MoS 2 (perpendicular and parallel to the plane of the substrate), growth on low shear substrates, i.e. the (002) plane parallel to the substrate, is usually preferred to obtain lower COF values.…”
Section: Introductionmentioning
confidence: 99%
“…It can be noticed that the curved MoS 2 nanosheets can avoid unidirectional shearing at large scales by extending the plane into a three-dimensional space, contributing to the improvement of mechanical properties . In addition, patterning metals into a periodically modulated nanomultilayered architecture is a commonly known path for strengthening metal materials compared with their monolithic counterparts. , Because the existence of a large number of laminated interfaces can be conducive to obstacles, dislocation mobility, and crack propagation. , More importantly, of the two basal planes typically present in MoS 2 (perpendicular and parallel to the plane of the substrate), growth on low shear substrates, i.e. the (002) plane parallel to the substrate, is usually preferred to obtain lower COF values. , It has been reported that the construction of alternating nanomultilayers involving MoS 2 sublayers can limit growth to the nanoscale while encouraging MoS 2 to grow parallel to the plane of the substrate, which can further yield superior tribological properties. , Therefore, if the MoS 2 nanosheets can be constructed as curved configuration and be periodically inset into refractory HEA film, then the cooperation of curved MoS 2 effects and the nanomultilayered feature may pave an effective route to improve tribological properties and mitigate the hardness loss.…”
Section: Introductionmentioning
confidence: 99%
“…Severe Plastic Deformation (SPD) processes are promising through making fine-grained bulk metallic materials [ 1 , 2 ]. Among many SPD grain refinement processes, Accumulative Roll Bonding (ARB) is one of the most prominent procedures with a wide variety of applications, gaining a great deal of attraction in recent decades [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The process shows an increasing attention owing to its feasibility of producing one main metallic matrix [ 6 , 13 ] and two or more different metallic matrix [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ] composites.…”
Section: Introductionmentioning
confidence: 99%